Influência de fatores do pré-abate de suínos sobre o PH inicial: estudo de caso - Souza, Pollyana Figueiredo Alves de (2022)
Pork is the most consumed source of animal protein in the world and is used in several meat products. It is known that the quality of the meat can be influenced by several factors, being pre-slaughter handling one of the main factors associated with the occurrence of loss of quality. Factors associated with the occurrence of stress can cause important muscle biochemical changes, which decisively interfere with the process of transformation of the muscle into the meat and consequently in the quality. One of the ways to measure the quality of pork meat in practice is to monitor pH values once this parameter is related to changes in color, texture (tenderness and juiciness, for example), water retention capacity, shelf life, or even processing. This study was conducted in a commercial slaughterhouse to evaluate the incidence of PSE (Pale, Soft, and Exudative) meat indicative in swine carcasses according to pre-slaughter handling conditions. For this, 4449 pH and temperature data were collected from the carcasses 45 minutes after slaughter (bleeding). The variables evaluated were: transport distance (up to 100km, between 101 and 200km, between 201 and 300km and above 300km), transport time (up to 3 hours, between 3 and 6 hours, between 6 and 9 hours, between 9 and 12 hours and above 12 hours), load density (below 0.35kg/m2, between 0.35 and 0.40 kg/m2, between 0.41 and 0.45 kg/m2 and above 0.45 kg/m2), fasting time (up to 24 hours and above 24 hours), resting time (up to 3 hours, between 3 and 6 hours, between 6 and 9 hours, between 9 and 12 hours, and over 12 hours), average weight (under 100kg, between 100 and 110kg, between 110,1 and 120kg, and over 120kg), the average temperature in the resting area (up to 24°C and over 24°C), and maximum temperature in the resting area (under 24°C, between 24 and 28°C, between 28,1 and 32°C, and over 32°C). From the pH45 values obtained, the carcasses were classified as Normal and PSE. The carcass was classified as normal when it presented pH45 ≥ 5.90 and susceptible to the occurrence of PSE when it presented pH45< 5.90. The results showed a significant difference between the values of fasting and the average temperature in the resting area in the incidence of carcasses predisposed to the occurrence of PSE. In cases of fasting above 24 hours, there was a 1.41 times greater probability of occurring carcasses with a predisposition to PSE meat. For average temperatures above 24°C, the probability was 1.52 times. The other parameters evaluated did not show significant differences in the occurrence of PSE meat.